2024
DOI: 10.1002/mco2.476
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol metabolism: physiological regulation and diseases

Jiarui Guo,
Silong Chen,
Ying Zhang
et al.

Abstract: Cholesterol homeostasis is crucial for cellular and systemic function. The disorder of cholesterol metabolism not only accelerates the onset of cardiovascular disease (CVD) but is also the fundamental cause of other ailments. The regulation of cholesterol metabolism in the human is an extremely complex process. Due to the dynamic balance between cholesterol synthesis, intake, efflux and storage, cholesterol metabolism generally remains secure. Disruption of any of these links is likely to have adverse effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 244 publications
(417 reference statements)
0
2
0
Order By: Relevance
“…The Srebp1 and Srebp2 have a bHLH-Zip region and ∼45% amino acid homology. In both of these proteins, the N-terminal side translocates to the nucleus and exerts transcription factor activity, and Srebp2 activates genes mainly encoding cholesterol and LDL receptors ( Guo et al, 2024 ). Srebp2 is regulated by post-translational modifications and it has been reported that nSrebp2 is degraded by the ubiquitin-proteasome system as a contributing factor to loss of function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Srebp1 and Srebp2 have a bHLH-Zip region and ∼45% amino acid homology. In both of these proteins, the N-terminal side translocates to the nucleus and exerts transcription factor activity, and Srebp2 activates genes mainly encoding cholesterol and LDL receptors ( Guo et al, 2024 ). Srebp2 is regulated by post-translational modifications and it has been reported that nSrebp2 is degraded by the ubiquitin-proteasome system as a contributing factor to loss of function.…”
Section: Discussionmentioning
confidence: 99%
“…Srebp2 is synthesized as a precursor and processed into a mature nuclear form (nSrebp2) in the Golgi apparatus before becoming a functional transcription factor. In the nucleus, nSrebp2 regulates the expression of many genes involved in cholesterol homeostasis ( Guo et al, 2024 ). Srebp2 activity has also been reported to be reduced in neurodegenerative diseases such as Alzheimer’s disease ( Mohamed et al, 2018 ; Tang et al, 2023 ), and Srebp2 has been reported to play an important role in the supply of cholesterol required for myelination ( Zhou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%